2022
DOI: 10.1021/acs.est.2c03403
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Controls on the Extent and Type of Metal Retention in Fine-Grained Sediments of a Simulated Aquifer

Abstract: Aquifer groundwater quality is largely controlled by sediment composition and physical heterogeneity, which commonly sustains a unique redox gradient pattern. Attenuation of heavy metals within these heterogeneous aquifers is reliant on multiple factors, including redox conditions and redox-active species that can further influence biogeochemical cycling. Here, we simulated an alluvial aquifer system using columns filled with natural coarse-grained sediments and two domains of finegrained sediment lenses. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Thus, additional knowledge is needed about the relevance of colloidal transport and exported reactivity for ground and surface water quality and for RTMs to include colloidal transport at the field scale. As an example, Babey et al showed, through RTM simulations based on data from a series of dual-domain column experiments, ,,, the necessity to consider transport of NOM colloids from anoxic environments as the key driver to explain the observed biogeochemistry downstream in an initially oxic surrounding environment. Indeed, the NOM colloidal transport from anoxic lenses to the oxic surrounding sediment drives the development of proximal secondary reduction zones (“halos”), characterized by high microbial activity (e.g., sulfate reduction) and accumulation of reduced reaction products (e.g., iron sulfide). , This study corroborates that neglecting colloidal transport within and from redox-dynamic environments creates major uncertainties in model simulations of pore, ground, and surface water quality.…”
Section: Current State Of Colloidal Transport Modeling and Associated...mentioning
confidence: 99%
“…Thus, additional knowledge is needed about the relevance of colloidal transport and exported reactivity for ground and surface water quality and for RTMs to include colloidal transport at the field scale. As an example, Babey et al showed, through RTM simulations based on data from a series of dual-domain column experiments, ,,, the necessity to consider transport of NOM colloids from anoxic environments as the key driver to explain the observed biogeochemistry downstream in an initially oxic surrounding environment. Indeed, the NOM colloidal transport from anoxic lenses to the oxic surrounding sediment drives the development of proximal secondary reduction zones (“halos”), characterized by high microbial activity (e.g., sulfate reduction) and accumulation of reduced reaction products (e.g., iron sulfide). , This study corroborates that neglecting colloidal transport within and from redox-dynamic environments creates major uncertainties in model simulations of pore, ground, and surface water quality.…”
Section: Current State Of Colloidal Transport Modeling and Associated...mentioning
confidence: 99%
“…Redox gradient magnitude also determines the fate of S in sediments with anoxic microsites. Sulfate reduction yields less energy to microorganisms than other electron acceptors, and therefore, SO 4 2– reduction is often limited or inhibited by other electron acceptors of higher redox potential. , Thus, anoxic microsites with mild redox gradients are less likely to support SO 4 2– reduction and S 2– generation than similarly sized anoxic microsites with sharper redox gradients. Gradient magnitude also dictates the distance S 2– species must travel to encounter oxidizing conditions.…”
Section: Influence Of Anoxic Microsites On Biogeochemical Cyclesmentioning
confidence: 99%
“…One way to get around the considerable technical difficulties in detecting and characterizing anoxic microsites and their influence is to construct laboratory analogues of varying complexity, such as no-flow/capillary-fringe incubation reactors, , diffusion-limited flow reactors, ,, flow-through columns/reactors with dual-flow regimes, ,,,, and microfluidic systems. , In these systems, distinct redox zones of various dimensions and composition are created by permeability contrasts (e.g., by inserting a diffusion-limited aggregate/lens within an advection dominated domain ,,,, ). Within these distinct zones, anoxic microsites are established in response to variation in flow and exchange rates in reactors ,,, or microfluidic systems .…”
Section: Techniques For Characterizing Anoxic Micrositesmentioning
confidence: 99%